2022
DOI: 10.1136/bmjopen-2021-056909
|View full text |Cite
|
Sign up to set email alerts
|

Are ethnic differences, urinary iodine status, lead and cadmium exposure associated with thyroid autoimmunity and hypothyroid status? A cross-sectional study

Abstract: ObjectiveWe aimed to evaluate the effects of different ethnicities and potential environmental exposure on the prevalence of thyroid autoimmune status and hypothyroid status.DesignThe data were obtained from two cross-sectional studies.Participants2105 participants in Shanghai (Han) and 772 participants in Yunnan Honghe Prefecture (Han, Yi, Miao and Hani), aged 18–75 were enrolled.MethodsParticipants underwent several checkups, including urinary iodine concentration, blood lead (BPb) and blood cadmium (BCd), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…As far as we know, only three previous studies have investigated the relationship between blood Cd exposure and thyroid function, two studies in China [ 22 , 23 ] and one study in Korea [ 24 ] consistently indicated that higher blood Cd was associated with higher risk of hypothyroidism, which was consistent with our findings in the study measuring urinary Cd concentrations (OR = 1.31). However, no significant association between blood Cd and hypothyroidism was observed in our study measuring blood Cd concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As far as we know, only three previous studies have investigated the relationship between blood Cd exposure and thyroid function, two studies in China [ 22 , 23 ] and one study in Korea [ 24 ] consistently indicated that higher blood Cd was associated with higher risk of hypothyroidism, which was consistent with our findings in the study measuring urinary Cd concentrations (OR = 1.31). However, no significant association between blood Cd and hypothyroidism was observed in our study measuring blood Cd concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, an occupational Cd exposure study in Italy observed negative correlation between urinary Cd levels and free triiodothyronine (FT3) and free thyroxine (FT4) and positive correlation between urinary Cd and thyroid stimulating hormone (TSH) levels [19]. In addition, three studies have revealed a positive association between blood Cd and the risk of hypothyroid status [22][23][24]. It is of note that no study has explored the association between urinary Cd and thyroid dysfunction, and few studies have veri ed their conclusions by using both urinary Cd and blood Cd measures which re ect long-term exposure and short-term exposure, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…Iodized salt helps prevent goiter and other thyroid conditions. However, supplemental dietary iodine has also been shown to increase the incidence of thyroid autoimmunity [22][23][24][25].…”
Section: Iodinementioning
confidence: 99%